Adaptive radiation of barbs of the genus Labeobarbus (Cyprinidae) in an East African river. (19th July 2019) - Levin, Boris A.; Casal‐López, Miriam; Simonov, Evgeniy; Dgebuadze, Yuri Y.; Mugue, Nikolay S.; Tiunov, Alexey V.; Doadrio, Ignacio; Golubtsov, Alexander S.
Abstract: Large African barbs of the genus Labeobarbus constitute a hexaploid lineage (2 n = 150). This group is widely distributed in African freshwaters, and exhibits profound phenotypic variation that could be a prerequisite for adaptive radiation. Using morphological, molecular, and stable isotope analyses, we investigated whether an adaptive radiation has occurred in a riverine assemblage of the Labeobarbus gananensis complex. This complex is composed of six phenotypically distinct sympatric forms inhabiting the Genale River (Ethiopian highlands, East Africa) in the Juba and Wabe–Shebelle drainages (Indian Ocean basin). Of the six forms, five were divergent in their mouth morphology, corresponding to generalised, lipped, scraping (two forms), and large‐mouthed phenotypes. One form had no mouth specialisation, but differed from the others in body shape (short and deep body; short form). Stable isotope analysis revealed differences in 15 N among these forms, representing different foraging strategies (omnivorous, scraping, and piscivorous). Phylogenetic analysis of two mitochondrial DNA markers confirmed the monophyly of L. gananensis, suggesting an intra‐riverine radiation. However, the Genale assemblage appears to have originated through a combination of allopatric and sympatric events. Some of the specialised forms within the Juba and Wabe–Shebelle drainage originated independently from the local generalised forms in three different river regions. Each of these cases could be considered as a small species flock composed of two or three sympatric forms. Our study shows that adaptive radiation in rivers can be enhanced by a combination of sympatric speciation and temporal geographic isolation, leading to local sympatric speciation followed by migration.